Evaluasi Kebijakan Pemberdayaan Nelayan - Ika Sartika (Universitas Riau, 2011)
The objective of this research was to evaluate fishermen‟s empowerment policies inPangandaran District. There were many empowerment policies that have implemented toimprove fishermen‟s welfare. But in fact, its result has not been felt significantly yet. Qualitativeapproach and descriptive method were used in this research based on five components, they are:concept, procedure, process, outcome, and benefit. In-depth interview and observation were usedto collect qualitative data. Informent taken from fishermen, fish distribution actors, PUSKUDMina‟s aparat, Fishermen Cooperaton aparat, and Fisheries and Marine Services of CiamisRegency were purposive selected in order to get comprehensive data. Data were analyzedthrough reduction, display, and conclusion drawing steps. Results of this study show that thereare no significantly benefits that can increase fishermen‟s welfare in long term. It was necessaryto find out well-concepted policy alternatives that can eradicate poverty root in fishermenvillages. One of policy alternative that can be tried was government intervention on fish farms. Itcan be traditionally approach or fishery industry cluster approach. Both of them should considerthe ideal future condition and the existing condition of fishermen, in order to get optimal resultof empowerment program.